2019
DOI: 10.31080/asor.2019.02.0122
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femur Replacement Mega prosthesis as A Salvage Measure in Non Malignant Conditions of the Knee Joint

Abstract: Total knee arthroplasty (TKA) is one of the most common orthopedic surgeries performed worldwide [1]. TKA has proved to be a successful and cost-effective treatment for improving pain and function in patients with advanced knee arthritis. There are situations in which not only joint surfaces have to be refashioned but also adjacent bone has to be replaced and thus preclude the usage of regular TKA prosthesis. Such conditions need Mega prosthesis more often than not. Mega prosthesis has majorly been used in ma-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…From the results of that study, Rajasekaran et al 18 concluded that megaprosthesis replacement in the distal femur in this group of elderly patients permited immediate full weight-bearing and allowed the patients to return to an adequate functional condition. The same conclusion was reached by Dwivedi et al 19 In their study, 10 patients (mean age of 71.2 yr), who were suffering from nononcological conditions, underwent distal femoral replacement using megaprosthetic replacement. They stated that using megaprosthesis replacement is an effective choice for the management of elderly patients with deficient bone stock.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…From the results of that study, Rajasekaran et al 18 concluded that megaprosthesis replacement in the distal femur in this group of elderly patients permited immediate full weight-bearing and allowed the patients to return to an adequate functional condition. The same conclusion was reached by Dwivedi et al 19 In their study, 10 patients (mean age of 71.2 yr), who were suffering from nononcological conditions, underwent distal femoral replacement using megaprosthetic replacement. They stated that using megaprosthesis replacement is an effective choice for the management of elderly patients with deficient bone stock.…”
Section: Discussionsupporting
confidence: 75%
“…They stated that using megaprosthesis replacement is an effective choice for the management of elderly patients with deficient bone stock. 19 A big limitation of endoprosthesis studies is the limited number of patients because of the rare surgical indications for usage. Barry et al 5 mentioned in a study that endoprosthesis should only be used as a last resort for the most severely affected patients with extensive bone loss, who represent around only 2.4% of revision TKA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation